2022
DOI: 10.1007/s41230-022-2001-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of V and Sn on microstructure and mechanical properties of gray cast iron

Abstract: The performance of an engine is significantly impacted by the quality of the cylinder liner, one of its key components. Gray cast iron has low cost (20%-40% cheaper than steel) and many desirable properties such as good castability, machining property, and wear resistance [1][2][3][4][5][6] . Due to the special graphite morphology, gray cast iron has a perfect combination of good mechanical properties and thermal conductivity, therefore, is widely used in engine cylinder liners [7,8] . With the rapid developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Adding various alloying elements can improve the mechanical properties of gray cast iron while satisfying the requirements of harsh working conditions [16][17][18][19]. For instance, Zhou et al [20] found that adding copper helps obtain austenite and bainite microstructures through a three-step heat treatment process, improving the material's yield and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Adding various alloying elements can improve the mechanical properties of gray cast iron while satisfying the requirements of harsh working conditions [16][17][18][19]. For instance, Zhou et al [20] found that adding copper helps obtain austenite and bainite microstructures through a three-step heat treatment process, improving the material's yield and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…The best way to increase the tensile strength of grey cast irons is to add alloying elements to change their microstructure [27][28][29]. Common alloying elements in these grey cast irons are molybdenum (Mo), niobium (Nb), vanadium (V), copper (Cu), tin (Sn), chromium (Cr) and so on [27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%